Local community attitudes and perceptions towards benefits and challenges associated with biodiversity conservation in Blouberg Nature Reserve, South Africa - Rampheri, Mangana B.; Dube, Timothy; Shoko, Cletah; Marambanyika, Thomas; Dhau, Inos (Wiley, 2022)
This study assessed the benefits and challenges associated with local community involvement in biodiversity conservation in the Blouberg Nature Reserve (BNR) of South Africa. To achieve this, a descriptive research design was used in the study. Three hundred and thirty-five households from four villages scattered around the nature reserve were selected using a stratified systematic sampling procedure to participate in a household questionnaire survey. The BNR Manager was purposefully selected for an in-depth structured interview so that an overview of socio-economic benefits and challenges to the community from the park's perspective could be known. Field data collection was conducted during the month of June 2019. Descriptive and inferential statistical methods as well as thematic analysis were used to analyse the field data. The main study findings indicated that the community members do not obtain sufficient socio-economic benefits from the nature reserve. The majority of the household respondents (89.6%) were not participating in biodiversity conservation in the nature reserve, despite possessing knowledge about nature conservation. The chi-square test results showed a significant association between household respondents’ conservation involvement and access to natural benefits (p = 0.008), and not cultural benefits (p = 0.740). Moreover, the chi-square test results further show no significant association between household attributes (gender and age) and knowledge of the role of nature reserve (p > 0.05), whereas education had a bearing on the knowledge possessed by households (p < 0.05). Overall, the findings indicate the need for more community involvement to support biodiversity conservation within nature reserves.